Analisis Pengelolaan APBD dalam Mendukung Pencapaian Pembangunan Daerah di Kabupaten Lamongan - Pamungkas Rahmat Fariid Tegar; Jordan Marcello Al Farrel; Eva Hany Fanida; Melda Fadiyah Hidayat (Pustaka Digital Indonesia, 2026)
The management of the Regional Revenue and Expenditure Budget (APBD) is an important instrument for local governments in supporting the achievement of development and improving community welfare. The effectiveness of APBD management is not only seen from the amount of budget allocation and realization, but also from its relationship with development achievements in priority sectors, such as infrastructure, education, health, community economy, and public services. This study aims to analyze the management of the Lamongan Regency APBD in supporting the achievement of regional development, identify supporting and inhibiting factors for its implementation, and formulate efforts to increase the effectiveness of regional budget management. This study uses a qualitative descriptive method with a literature study approach and secondary data analysis. Data was obtained from Lamongan Regency APBD reports, data from the Central Statistics Agency (BPS), local government documents, scientific books, and relevant national journals. The results of the study show that the management of the Lamongan Regency APBD plays an important role in supporting regional development through budget allocation in the infrastructure, education, health, agriculture, fisheries, MSMEs, and public service sectors. Local governments have also begun to develop the digitalization of financial administration as an effort to increase transparency, accountability, and effectiveness of budget management. However, the effectiveness of APBD management still faces several obstacles, including delays in budget absorption in several Regional Apparatus Organizations, inequality in development between regions, limited quality of human resources of apparatus, and weak supervision of development programs. Therefore, it is necessary to strengthen data-based budget planning, increase the capacity of the apparatus, optimize regional financial digitalization, strengthen the supervisory system, and increase community participation so that regional development can run more equitable, transparent, accountable, and sustainable.